Mountains in motion, visions in nutshells (EAAE Annual Conference Proceedings, 2023)
Architectural research is defined as community practice and for communities. Architecture has always been constituted as a practice of settlement and territorial domestication for the community’s liveability of the places. This paper focuses on how architecture, in its dual form of discipline and utility, defines itself as a conspicuous part of ‘solid’ memory.